Pengaruh Fasilitas Belajar dan Motivasi terhadap Hasil Belajar Siswa Kelas 8 di SMP Negeri 1 Ketapang - Aviona Adisty; Devri Devri; Erdinawati Erdinawati; Adelina Fernanda Wati; Muliada Muliada (STIKes Ibnu Sina Ajibarang, 2023)
The education system in Indonesia places a high priority on continuous improvement. The amount of effort individuals put into their studies, as well as the available resources, may impact their level of success. The aim of this research is to understand how the learning outcomes of students at SMPN 1 Ketapang in subjects related to Informatics are influenced by factors such as learning facilities and their desire to learn. The research approach used is multiple linear regression testing. This study includes a representative sample of 48 students from the 2nd grade of junior high school. The findings of this research indicate that learning outcomes are strongly influenced by students' level of desire to learn or motivation. However, learning outcomes are not affected by learning facilities. Nevertheless, both learning facilities and motivation significantly contribute to better learning outcomes when considered simultaneously.